A short-term based analysis on the critical low carbon technologies for the main energy-intensive industries in China. (10th January 2018) - Wang, Nannan; Chen, Xiaoyan; Wu, Guobin; Chang, Yen-Chiang; Yao, Shengnan
Abstract: The thermal power industry, the cement industry and the iron & steel industry are among the top energy consumers and air-polluters in China, which have significant impacts on climate change. The annual productions of these three industry sectors are all ranked as the top one in the world. In order to assist the short-term policy making for the development of critical LCTs in China, an evaluation of the performance of low carbon technologies (LCTs) for the top three energy-intensive industries in China is conducted in this paper through multi-criteria decision making (MCDM) method. There are 31 LCTs identified for these three industries based on the criteria including environmental performance, technological performance, and economic performance. Based on the experts' evaluation, top 10 LCTs are selected as the critical LCTs which should be given priority in the short-term technology diffusion in China. Suggestions are provided for policy-makers on the carbon mitigation and cleaner production in the main energy-intensive industries in China.